Effect of the dietary inclusion of a natural zeolite (clinoptilolite) on aerial ammonia level in pig houses - SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ) K.; ALEXOPOULOS (Κ. ΑΛΕΞΟΠΟΥΛΟΣ) C.; PAPAIOANNOU (Δ.Σ. ΠΑΠΑΪΩΑΝΝΟΥ) D. S.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K.; KYRIAKIS (Σ.K. ΚΥΡΙΑΚΗΣ) S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
The beneficial effect of dietary inclusion of natural zeolites on the growth of the animals and on reducing ammonia levels in livestock buildings, has been escribed. The objective of the present study was to determine the effect of the dietary inclusion of a natural zeolite (clinoptilolite) on the ammonia level in a Greek "farrow-to-finish" pig unit. Animals participating in the study were of the same genetic background and were divided into two main experimental groups depending on the inclusion or not of clinoptilolite (groups Ζ and Νrespectively) and four experimental subgroups depending on the inclusion or not of antimicrobials in the feed (subgroups Zl9 Nx and Z2, N2 respectively). Aerial ammonia level measurements were carried out using diffusion tubes (Dräger tubes) at the end of each growth stage (weaning, growing and fattening stages). In order to ensure the accuracy of the measurements, in each barn, animals of the same experimental subgroup were allocated. The results of this study demonstrate that the incorporation of clinoptilolite in swine feed had a favorable effect on aerial ammonia level. Significantly lower levels (P<0,05) were obtained in Zl subgroup at the end of the fattening stage. Comparing the results among the main experimental groups (Z and N), the decreasing effect on ammonia level (P<0,05) was evident at the end of the growing and the fattening stages.